2016
DOI: 10.2175/106143016x14504669768895
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Equilibrium Calculations on Cd Transformation during Sewage Sludge Incineration

Abstract: Thermodynamic equilibrium calculations were performed to reveal the distribution of cadmium during the sewage sludge incineration process. During sludge incineration in the presence of major minerals, such as SiO2, Al2O3 and CaO, the strongest effect was exerted by SiO2 on the Cd transformation compared with the effect of others. The stable solid product of CdSiO3 was formed easily with the reaction between Cd and SiO2, which can restrain the emissions of gaseous Cd pollutants. CdCl2 was formed more easily in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…With the comparison of Figures 8a and 8b, the Cd forms, transformation and distribution were affected by mineral substances during the sludge incineration process (Xie et al,2010;Liu et al, 2016a). Figure 8b shows the equilibrium calculation results of Cd species in the temperature range of 400 to 1800 K in the presence of mineral substances.…”
Section: Resultsmentioning
confidence: 98%
“…With the comparison of Figures 8a and 8b, the Cd forms, transformation and distribution were affected by mineral substances during the sludge incineration process (Xie et al,2010;Liu et al, 2016a). Figure 8b shows the equilibrium calculation results of Cd species in the temperature range of 400 to 1800 K in the presence of mineral substances.…”
Section: Resultsmentioning
confidence: 98%
“…For example, “Treatment and Pollution Control Technology Policy for Sludge in Municipal Wastewater Treatment Plant” adopted by the Ministry of Environmental Protection of China incentivizes the use of sludge as a fuel in co‐incineration by thermal power plants, and cement and brick kilns. However, the complexity and variability of fuel components (e.g., sludge, coals, and municipal solid waste—MSW) in co‐incineration have led to the emissions of pollutants with strong toxicity such as heavy metals (HMs), organic pollutants, and acid gases (Li, Zhang, Shao, & He, ; Li et al., ; Liu, Fu, et al., ; Yu et al., ) whose migration, transformation, and emission patterns have drawn worldwide attention (Han, Hwang, Kim, Park, & Kim, ; Liu, Huang, et al, ; Liu, Huang, Sun, & Xie, ; Liu, Zeng, et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The migration and transformation patterns of multiple HMs in the co‐incineration system depend on incinerator type, operational conditions (e.g., incineration temperature, residence time, and combustion atmosphere) (Peng, Lin, & Wey, ; Roy, Dutta, Corscadden, Havard, & Dickie, ), initial sludge composition, Cl content of mixed wastes, and S content of coal (Liu, Fu, et al., ; Liu, Huang, et al., ; Liu, Zeng, et al., ; Liu et al., ). For example, the Cl‐containing compounds are easily reactive with Zn, thus producing HM chlorides and large Zn emissions (Fraissler, Jöller, Mattenberger, Brunner, & Obernberger, ; Saqib & Backstrom, ; Struis, Ludwig, Lutz, & Scheidegger, ; Stucki & Jakob, ).…”
Section: Introductionmentioning
confidence: 99%
“…In principle, sulfur can delay heavy metal volatilization when the incineration temperature is below 800°C (Verhulst et al 1996). Liu and Sun (2010b) and Liu et al (2012) conducted a theoretical study of heavy metal volatilization. However, a study performed by Hasan and Hermann (2000) indicated that a theoretical study could not predict the transformation of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the emission and leaching of Cd from ash have received considerable attention (Soria et al 2013;Liu et al 2013;Asthana et al 2010) as part of understanding the effects of different factors on heavy metal behavior characteristics on the basis of the thermodynamic equilibrium method. Previous studies (Liu and Sun 2010a;Fraissler et al 2009;Durlak et al 1997) on heavy metal control indicate that the thermodynamic equilibrium method is effective.…”
Section: Introductionmentioning
confidence: 99%